Nonlinear model predictive control for processes with complex dynamics: A parameterisation approach using Laguerre functions - Ławryńczuk, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
Classical model predictive control (MPC) algorithms need very long horizons when the controlled process has complex dynamics. In particular, the control horizon, which determines the number of decision variables optimised on-line at each sampling instant, is crucial since it significantly affects computational complexity.
Keywords: process control; nonlinear model predictive control; Laguerre functions; linearisation